Determination of amygdalin in fifteen different fruit kernels and extraction optimization - AYAZ SEYHAN, SERAP; BİLĞİÇ ALKAYA, DİLEK (My University, 2022)
Amygdalin (AMG) is mainly an alternative therapy for traditional cancer treatment. In this study, an effective HPLC-DAD method was developed to investigate the extraction efficiency and determine AMG levels in fifteen fruit kernels belonging to different families. AMG in bitter almond was extracted from using various solvents by different extraction methods (Soxhlet, ultrasonic, orbital shaking and microwave extraction). The most suitable method was determined by the optimized HPLC-DAD method and was applied to fifteen different fruit kernels. The recoveries were in the range 94.68% to 95.26%. The LOD and LOQ values were 0.0097 mg/g and 0.0295 mg/g, respectively. The amygdalin content in kernel fruits was determined ranging from 0.074 to 65.21 mg/g. This study showed that AMG was determined in a short time and with high yield, and the presence of AMG was proven in other fruit kernels belonging to different families that had not been proven before.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Natural Sciences (SCI); CHEMISTRY; Genel Kimya; Fizik Bilimleri; General Chemistry; Physical Sciences